ALGORITHMS OF LANGUAGE IN SPEECH BY THE PRESIDENT OF REPUBLIC INDONESIA - Santoso, Dwi; Apriyanto, Sigit (International Journal of Psychosocial Rehabilitation, 2020)
Political genre analysis has for a long time been the focus of consideration for many researchers as they fund a rich source of discovery about the nature of language handling due to their organized and well-established structure. While politicians or president may be interested in how to gain the provision from the public, linguists and critical discourse, analysts might be interested in the way such support is enacted by language. In this paper, I would like to analyse Indonesian President Joko Widodo’s speech from the perspective of algorithms language. In particular, I shall discover the idea that this speech is constructed by analytical thinking, clout, and authentic. The text files were prepared for LIWC analysis according to the speech transcripts to compute the percentages of analytical thinking, clout, and authentic-related words used by the President Joko Widodo during his speech. The findings show that Joko Widodo was used 98,26% (high) or 1,74% (low) on analytical thinking, 77,79% (high) or 22,21% (low) on clout, and 13,48% (high) or 86,52% (low) on authentic. The findings can be used both for applied linguists interested in discourse analysis and language practitioner interested in the use of critical discourse approaches to the analysis of speaking skill.